Optimized cultivation of porcine choroid plexus epithelial cells, a blood-cerebrospinal fluid barrier model, for studying granulocyte transmigration - Lauer, Alexa; März, Martin; Meyer, Svenja; Meurer, Marita; Buhr, Nicole de; Borkowski, Julia; Weiß, Christel; Schroten, Horst; Schwerk, Christian (Laboratory investigation, 2019)
A porcine in vitro model of the blood-cerebrospinal fluid barrier based on choroid plexus epithelial cells was optimized for culture on cell culture filter inserts to prevent growth of the cells through filter pores. The optimized model retained barrier function and allowed improved investigation of porcine granulocyte transmigration across the cell layer.
Gesehen am 16.01.2020
Received: 15 November 2018